Design and Implementation of an USV for Large Bodies of Fresh Waters at the Highlands of Peru - Balbuena, J (2017)
The following paper describes the design, implementation and preliminary tests of an Unmanned Surface Vessel (USV) robot, able to collect water quality parameters and bathymeter measurements in lakes and bodies of fresh water at the Peruvian highlands. The USV robot is developed in order to be a measurement tool to monitor water pollution and help to improve the current methods used for this task. The USV integrates a video system which is used to maneuver the robot, a multiparameter probe for measuring water quality parameters (temperature, pH, dissolved oxygen, turbidity, conductivity and colored dissolved organic matter), a bathymeter to obtain depth measurements, and a wireless outdoor base station to create a wireless local area network through which the data is received and transmitted. The preliminary results of the performance of the USV are obtained from a lake located in the Peruvian highland at an altitude above of 4000 m.a.s.l. The main reason is the possible increasing water pollution caused by the presence of a hydroelectric power plant, mining industries and touristic activities near the surroundings and the sources of water for the lakes.